ATP1A3-Related Disorders: An Ever-Expanding Clinical Spectrum - Salles, Philippe A.; Mata, Ignacio F.; Brünger, Tobias; Lal, Dennis; Fernandez, Hubert H. (Frontiers in Neurology, 2021)
The Na+/K+ ATPases are Sodium-Potassium exchanging pumps, with a heteromeric α-β-γ protein complex. The α3 isoform is required as a rescue pump, after repeated action potentials, with a distribution predominantly in neurons of the central nervous system. This isoform is encoded by the ATP1A3 gene. Pathogenic variants in this gene have been implicated in several phenotypes in the last decades. Carriers of pathogenic variants in this gene manifest neurological and non-neurological features in many combinations, usually with an acute onset and paroxysmal episodes triggered by fever or other factors. The first three syndromes described were: (1) rapid-onset dystonia parkinsonism; (2) alternating hemiplegia of childhood; and, (3) cerebellar ataxia, pes cavus, optic atrophy, and sensorineural hearing loss (CAPOS syndrome). Since their original description, an expanding number of cases presenting with atypical and overlapping features have been reported. Because of this, ATP1A3-disorders are now beginning to be viewed as a phenotypic continuum representing discrete expressions along a broadly heterogeneous clinical spectrum.